Fault detection and identification scheme using neural network - Than Soe. (2008)
This dissertation presents a Fault Detection and Identification Scheme of an aircraft control system based on a feedforward neural network. The training scheme for the neural network uses the standard backpropagation algorithm. The aircraft model used is that of a high performance fighter aircraft and only the longitudinal linear model is considered in this study.